ANALISIS PENGARUH INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA TAHUN 2015-2020 - Muhammad, Fuady; Ashar, Khusnul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Economic Development have a main target that is increase well-being society . Success development economy can be measured from how much good country the when face something problem and could solve problem that . one _ cases found _ almost every _ Indonesian territory is height number unemployment . On Year 2020 level unemployment increase in band year previous 2019, Rise number unemployment in a country will take effect on growth and economy in a country that . Besides limited field profession and the minimum power skilled work _ there is also inflation , explosion population and also lack of investment that becomes wrong one enhancing aspects _ amount unemployment . Study this aim for knowing how influence from Investation to Absorption Power Formal Work in Indonesia so that later could help government for reduce level unemployment in Indonesia. Study this use method analysis simple linear regression data pandel with year 2015-2020 research . Results study this show that Investation take effect positive and significant to Absorption Power Formal Work in Indonesia